Laser heating applications analytical modelling - Yilbas, B. S. (Elsevier, 2012)
Thermal treatment of materials occupies a significant, increasing proportion of MSE activity and is an integral component of modern curricula as well as a highly monetized component of industrial production. This work encompasses the basics of laser processing and provides an introduction to analytical modelling of the process.